The golden era of ocular disease gene discovery: Race to the finish. (9th July 2013) - Swaroop, A; Sieving, P A
<x xml:space="preserve">Abstract</x> Within the last decade, technological advances have led to amazing genetic insights into Mendelian and multifactorial ocular diseases. We provide a perspective of the progress in gene discovery and discuss the implications. We believe that the time has come to redefine the goals and begin utilizing the genetic knowledge for clinical management and treatment design. The unbelievable opportunities now exist for those nimble enough to seize them.